Atrazine exposure improves the proliferation of H22 cells in vitro and in vivo. Issue 39 (13th June 2018) - Tian, Yong; He, Jingchun; Liu, Nan; Huang, Di; Liu, Zhuo; Yang, Yanrong; Chen, Junyu; Zhao, Benzheng; Zhao, Shuhua; Liang, Bing
Abstract : ATZ exposure promotes tumor proliferation and metastasis. Abstract : Atrazine (ATZ), a widely used triazine herbicide, has been detected in the surface and ground water even far from where it is applied. Recently, the biotoxicity of atrazine to the immune, reproductive and endocrine systems has been preliminarily observed in laboratory experiments and epidemiological research studies. In order to further comprehend the carcinogenic nature of ATZ, in vitro and in vivo models were established in this study to explore the effects of ATZ exposure on hepatocellular carcinoma. The results showed that after being treated with ATZ, the proliferation of H22 cells increased, and the tumor volume and amount of ascites were significantly increased in an in situ transplantation tumor model established in C57BL/6 mice compared to the control group. The expression of p53 was down-regulated, while the expression of cyclin-D1, VEGF, MMP2, Stat3 and C-myc was up-regulated in the ATZ-treated groups compared to the control group. These results indicate that ATZ might activate the Stat3 signaling pathway and promote the proliferation and invasion of hepatocellular carcinoma cells.